Math, asked by bscroggins4517, 1 year ago

–p^2(p – 11)
simplify product


bscroggins4517: PLease please hurry!!!
bscroggins4517: I WILL MARK BRAINLEST WHO GIVE WRITE ANSWER
bscroggins4517: hey :) :)
jayapundir29: Answer toh de diya hai..
bscroggins4517: great how about you

Answers

Answered by jayapundir29
1
Heyaaaa !!!

❤❤ ♡♡ ♥ ♡♡❤❤

=  -p^2  (p - 11 )

=  -p^3 +  11p

...

☺☺

Thanks...

Prabhnoorsinghrehal: hi
jayapundir29: Hii
Prabhnoorsinghrehal: how are you
jayapundir29: always fyn
Prabhnoorsinghrehal: ok
Prabhnoorsinghrehal: in which class are you
Prabhnoorsinghrehal: hi
Answered by hafizur0210
0

Answer:

2P²(P-11)

=2P³-22P²

=2p³-22p²+0.x+0

=2p²(p-11)+0(p-11). [Sins, 0(p-11)=0]

=(p-11)(2p²+0)

Either,p-11=0. Or, 2p²+0=0

»p=11. »2p²=0

»p²=0

»p=0


bscroggins4517: you are really late already got the problem wrong
Similar questions